A process model recognising prior learning of informal sector motor mechanics - Jordaan, C.J.; Bezuidenhout, A.; Schultz, C. (South African Journal of Higher Education, 2018)
<span style="line-height: 115%; font-family: 'Arial',sans-serif; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-ZA; mso-fareast-language: EN-ZA; mso-bidi-language: AR-SA;">The informal sector serves as a reservoir of skilled unqualified individuals who learned and practice the motor mechanic trade outside the formal sector. This article reports on a process model for recognition of prior learning of informal sector motor mechanics and to integrate them into the formal sector training and ultimately employment. F<span style="line-height: 115%; font-family: 'Arial',sans-serif; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-ZA; mso-fareast-language: EN-ZA; mso-bidi-language: AR-SA;">ormal sector motor mechanic training does not acknowledge non-formal learning of the informal sector.<span style="line-height: 115%; font-family: 'Arial',sans-serif; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-ZA; mso-fareast-language: EN-ZA; mso-bidi-language: AR-SA;">The process model identifies specific entry points into the formal sector training.<span style="line-height: 115%; font-family: 'Arial',sans-serif; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-ZA; mso-fareast-language: EN-ZA; mso-bidi-language: AR-SA;">The study was exploratory in nature with a qualitative research design applied. Semi-structured interviews through a<span style="line-height: 115%; font-family: 'Arial',sans-serif; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-ZA; mso-fareast-language: EN-ZA; mso-bidi-language: AR-SA;"> purposive snowball sample technique were used<span style="line-height: 115%; font-family: 'Arial',sans-serif; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-ZA; mso-fareast-language: EN-ZA; mso-bidi-language: AR-SA;">. The data were analysed utilising the ATLAS.ti 7.0 program. The <span style="line-height: 115%; font-family: 'Arial',sans-serif; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-ZA; mso-fareast-language: EN-ZA; mso-bidi-language: AR-SA;">findings conceptualises a process model, backed by a process of gap training, to recognise the prior learning of the informal sector motor mechanic. This research<span style="line-height: 115%; font-family: 'Arial',sans-serif; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-ZA; mso-fareast-language: EN-ZA; mso-bidi-language: AR-SA;"> could engage SETAs in the funding of training of informal practising motor mechanics